Building Collaboration and Balancing Stakeholder Needs in Comprehensive Health and Guidance Programming - Collins, Sandra (Canadian Journal of Counselling and Psychotherapy, 2007)
Comprehensive Health and Guidance initiatives highlight the need for increased involvement of various stakeholder groups in identifying and meeting the emotional, social, academic, and physical needs of children and adolescents. The integration of multiple perspectives in program planning facilitates an understanding of differences and opens the door to collaborative decision making about program priorities as well as coordinated investment in program initiatives. Active involvement of students, in particular, beginning at the planning stages, fosters personal and collective empowerment and ensures that the programs created are relevant, responsive, and that they find the support they need to achieve optimum impact.